PERENCANAAN PENCAHAYAAN BUATAN PADA GEDUNG FAKULTAS TEKNIK UNIVERSITAS PATTIMURA AMBON - Buyang, Christy Gery; Sangadji, Fauzan A; Heriadi, Mul Fadia Fahira (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
This study aims to analyze and design the artificial lighting system of the Faculty of Engineering Building at Pattimura University, Ambon, to meet the standards specified in SNI 03-6575-2001. Measurements were carried out using a Lux Meter Kuber AS803 to obtain natural and artificial lighting data for each room across the building’s three floors. Primary data include room dimensions, lamp types and quantities, and existing conditions, while secondary data were obtained from literature and lighting standards. Analysis was conducted using DIALux Evo to determine the average illuminance level and assess compliance with SNI standards. The results show that most classrooms and lecturers’ rooms have lighting levels below the standard, with average illuminance values of 112,25 lux, whereas the minimum standard for classrooms is 250-350 lux. The low illumination levels are caused by limited lamp quantity and low lamp power. This study recommends adding more lighting points, increasing lamp wattage, and optimizing lighting layout through DIALux Evo simulation to meet the standard and improve visual comfort for users. Based on the analysis and planning results, the total cost required to meet the artificial lighting standard for the entire building is Rp 280,924,489.Keywords: Artificial lighting; Dialux evo; construction costs